2006
DOI: 10.1007/s11104-006-9037-z
|View full text |Cite
|
Sign up to set email alerts
|

Internal efficiency, nutrient uptake, and the relation to field water resources in rainfed lowland rice of northeast Thailand

Abstract: Rice-based (Oryza sativa L.) rainfed lowlands are the major cropping system in northeast Thailand. Average yields are low, which is generally explained by frequent drought events, low soil fertility, and poor fertilizer response. However, neither the relative importance of these factors nor their interaction is well understood. Therefore, we analyzed an existing database on fertilizer trials conducted between 1995 and 1997 at eight different sites in northeast Thailand with the objective to determine indigenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 21 publications
3
12
1
Order By: Relevance
“…In both studies the rice yields were relatively low (<4 t ha −1 ). The higher RIE reported for traditional-type rice by Naklang et al (2006) than found for semi-dwarf modern rice such as in Witt et al (1999) and our study resulted from differences in harvest index rather than differences in tissue concentration of nutrients between the two types of rice.…”
Section: Internal Nutrient Efficiencies For Ricecontrasting
confidence: 54%
See 1 more Smart Citation
“…In both studies the rice yields were relatively low (<4 t ha −1 ). The higher RIE reported for traditional-type rice by Naklang et al (2006) than found for semi-dwarf modern rice such as in Witt et al (1999) and our study resulted from differences in harvest index rather than differences in tissue concentration of nutrients between the two types of rice.…”
Section: Internal Nutrient Efficiencies For Ricecontrasting
confidence: 54%
“…Mukhopadhyay et al (2008), for example, in a fertilizer trial with rainfed rice in West Bengal in eastern India, reported mean harvest index=0.32 and mean accumulation of 33 kg K and 4.3 kg P per tonne of grain. In a multi-location trial in Thailand with 624 observations for traditional tall rice cultivars, Naklang et al (2006) reported median harvest index=0.28 and median plant accumulation of 48 kg K and 4.7 kg P per tonne of grain. In both studies the rice yields were relatively low (<4 t ha −1 ).…”
Section: Internal Nutrient Efficiencies For Ricementioning
confidence: 99%
“…In China, Zhang et al (2008b) reported iNUE of 9.7 for upland cotton that yielded up to 1,000 kg/ha. In comparison, Naklang et al (2006) reported iNUE of 46 kg rice grain/kg crop N uptake.…”
Section: Crop Inue Measurementsmentioning
confidence: 99%
“…Observed yields of the indica, japonica, indica × japonica and indica × javanica genotypes in tropical (averages for the locations Ubon and Chiangmai) and cool subtropical (location Iwate) environments. ity due to poor soil structure, and low pH [45,46]. The influence of different soil characteristics on yield may be further explored using simulation models.…”
Section: Genetic Adaptation For Yield Responses To Environmentmentioning
confidence: 99%